2019
DOI: 10.3390/su11071944
|View full text |Cite
|
Sign up to set email alerts
|

Does Identification Influence Continuous E-Commerce Consumption? The Mediating Role of Intrinsic Motivations

Abstract: The motivation behind online consumption behavior is different from that of online social behavior, and research is lacking regarding the impact of identification on e-commerce consumption. The current research examines the influence of identification, which is perceived anonymity, and intrinsic motivation on the continuous purchasing behaviors on retailing e-commerce websites based on self-determination theory. The mediating role of intrinsic motivation was also empirically tested from a sample of 661 frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 98 publications
(131 reference statements)
2
10
0
Order By: Relevance
“…Identifiability and perceived anonymity of SNS user identity are not two sides of an organic whole but, rather, two different elements (Chen et al, 2019a). Identifiability reflects the amount of information available on the real identity of the behavioral subject that is identified (Marx, 1999).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Identifiability and perceived anonymity of SNS user identity are not two sides of an organic whole but, rather, two different elements (Chen et al, 2019a). Identifiability reflects the amount of information available on the real identity of the behavioral subject that is identified (Marx, 1999).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…perception of the nature of the subject. Previous research has confirmed that identity has a significantly negative impact on perceptual anonymity on various online social media platforms (Chen et al, 2016(Chen et al, , 2019a. The relationship between these two factors should be the same in monitoring and participating in discussions on moral/ethical violation topics on online social media.…”
Section: Identification and Anonymity On Social Networking Sitesmentioning
confidence: 93%
See 3 more Smart Citations